Determinants Factor of the Captive Breeding success of Citron-crested cockatoo (Cacatua sulphurea citrinocristata, Fraser 1844) - Mery Fahik; Burhanuddina Masy'ud; Jarwadi B. Hernowo (Media Konservasi, 2018)
Citron-crested cockatoo (Cacatua sulphurea citrinocristata) is one of endemic bird which endangered in Sumba islands and protected by in law. The study was aimed to analyze the determinants factor of the captive breeding success of citron-crested cockatoo. The research was conducted in January-March 2018, in Mega Bird and Orchid Farm Bogor, Ragunan Zoo, Rahardjo Bird Farm Solo, and Cikembulan Zoo. Determinant factor of the captive breeding success of citron-crested cockatoo were analyze using PCA with SPSS 22 software. The main components which are important factors for captive breeding success of Citron-crested cockatoo were breeding techniques (feed, time of handling, the number of productive parent and capital), condition of citron-crested cockatoo cage (temperature and humidity) and human resources (duration time of the breeding and knowledge of the keeper). Keywords: captive breeding, citron-crested cockatoo,  principal component